Prevalence of Musculoskeletal Diseases of the Upper Extremity Among Dental Professionals in Germany - Rickert C; Fels U; Gosheger G; Kalisch T; Liem D; Klingebiel S; Schneider KN; Schorn D (Dove Medical Press, 2021)
Carolin Rickert,1,* Ulrike Fels,1,* Georg Gosheger,1 Tobias Kalisch,1 Dennis Liem,2 Sebastian Klingebiel,1 Kristian Nikolaus Schneider,1 Dominik Schorn1 1Department of General Orthopedics and Tumor Orthopedics, Münster University Hospital, Münster, Germany; 2Sporthopaedicum Berlin, Berlin, Germany*These authors contributed equally to this workCorrespondence: Carolin RickertDepartment of General Orthopedics and Tumor Orthopedics, Münster University Hospital, Albert-Schweitzer Campus 1, Gebäude A1, Münster, 48149, GermanyEmail carolin.rickert@ukmuenster.deObjective: Although many findings on occupational musculoskeletal complaints are available from American and European dentists, the corresponding data from Germany are still scarce. Therefore, the aim of this study was to provide additional information on the prevalence of and risk factors for musculoskeletal disorders of the upper extremity, particularly the shoulder in this specific population.Methods: A written survey was carried out among 600 dentists in the state of North Rhine-Westphalia, Germany. Questionnaire items included physical and psychosocial workload, general health, and the occurrence of musculoskeletal symptoms during the previous 12 months that led to sick leave and medical care according to a modified version of the Nordic Musculoskeletal Questionnaire (NMQ). Regression analysis was used to evaluate relevant risk factors for severe musculoskeletal disorders.Results: A total of 229 dentists were participated in the study (response rate 38%). Overall, 92.6% of the participants had already suffered from musculoskeletal symptoms in at least one body region. Symptoms were mostly reported in the neck (65.1%) and in the shoulder (58.1%). Limitations in daily activities were experienced by 15.9% due to neck pain and by 15.4% due to shoulder pain. Medical care was sought by 23.7% because of neck pain and by 21.1% due to shoulder pain. Risk factors for symptoms in the upper extremity regions were gender (female), increased physical load, and numerous comorbidities.Conclusion: There is a high prevalence of musculoskeletal disorders among dentists. Suitable interventions are therefore needed to prevent musculoskeletal diseases and pain among dental professionals, with particular attention to female dentists.Keywords: musculoskeletal disease, prevalence, dentists, risk factors, occupational exposure